From Design to Execution: S-Curve-Controlled Implementation of a Hybrid Urban Drainage System in West Pontianak - Saputra, Doddy Cahyadi; Santosa, Dimas Puji; Sugasta, Hervian Handika; Adibah, Fairuz; Rangga, Boy (Jurnal Teknik Sipil, 2025)
This study presents an integrated approach to optimizing urban drainage infrastructure in Gg. Smile, West Pontianak"”a flood-prone area facing increased hydraulic and environmental stress due to urbanization. Field observations revealed significant degradation in earthen drainage channels, prompting the development of a hybrid system that combines reinforced concrete with ecological features. The proposed design, implemented over six weeks, utilized concrete sheet piles, crossbeams, and biofiltration zones, resulting in a 300% increase in hydraulic capacity while maintaining 40% of the original infiltration potential. IoT-based monitoring systems were embedded for real-time flow surveillance and predictive maintenance. Cost analysis revealed financial feasibility, with material efficiency and safety compliance maintained throughout the project. Post-construction evaluation confirmed a 40"“60% reduction in pollutant loads and a 25% increase in groundwater recharge. The successful use of the S-curve for progress monitoring and resource allocation validated the project"™s management strategy. This study advocates for the replication of hybrid grey-green drainage systems across tropical urban centers, integrating structural resilience with environmental sustainability and intelligent monitoring.